2014
DOI: 10.1007/s12262-014-1179-2
|View full text |Cite
|
Sign up to set email alerts
|

High Ligation of Inferior Mesenteric Artery in Left Colonic and Rectal Cancers: Lymph Node Yield and Survival Benefit

Abstract: During surgery for colorectal cancer, the inferior mesenteric artery (IMA) may be ligated either directly at the origin of the IMA from the aorta (high ligation) or at a point just below the origin of the left colic artery (low ligation). Sixty patients of left colonic and rectal cancer undergoing elective curative surgery in 2007 and 2008 were selected for this observational study. The resected lymph nodes were grouped into three levels: along the bowel wall (D1), along IMA below left colic (D2), and along th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 14 publications
1
11
2
1
Order By: Relevance
“…Ligation of the inferior mesenteric artery (IMA) could be applied without any clinical consequences. Surgeons ligate IMA either directly at the origin of the IMA from the aorta (high ligation), or at a point just below the origin of the left colic artery (low ligation) [ 47 ]. There are two arterial arches between the middle colic artery (branch of the superior mesenteric artery) and the left colic artery (branch of the inferior mesenteric artery), which maximally keep the blood supply to the descending colon after high ligation of the IMA.…”
Section: Discussionmentioning
confidence: 99%
“…Ligation of the inferior mesenteric artery (IMA) could be applied without any clinical consequences. Surgeons ligate IMA either directly at the origin of the IMA from the aorta (high ligation), or at a point just below the origin of the left colic artery (low ligation) [ 47 ]. There are two arterial arches between the middle colic artery (branch of the superior mesenteric artery) and the left colic artery (branch of the inferior mesenteric artery), which maximally keep the blood supply to the descending colon after high ligation of the IMA.…”
Section: Discussionmentioning
confidence: 99%
“…In this included 5 studies, Slanetz and Grimson [ 7 ] and Charan [ 8 ] have shown the results in which the high ligation associated with more extensive resection of mesentery and its lymphatic drainage. It also has clinical significance to reduce local tumor recurrence and increases the oncological survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 20 cohort studies, 11 studies had high quality with achieving 7 or more stars. [19,20,24,25,28,32,34,36,37,40,41] The 4 RCTs had medium or high quality. [22,30,31,39]…”
Section: Quality Judgment Of Studiesmentioning
confidence: 99%